Essentials of scientific computing : numerical methods in science and engineering - Zalizniak, Victor (Horwood Pub., 2008)
Modern development of science and technology is based to a large degree on computer modelling. To understand the principles and techniques of computer modelling, students should first get a strong background in classical numerical methods, which are the subject of this book. This text is intended for use in a numerical methods course for engineering and science students, but will also be useful as a handbook on numerical techniques for research students. Essentials of Scientific Computing is as self-contained as possible and considers a variety of methods for each type of problem discussed. It covers the basic ideas of numerical techniques, including iterative process, extrapolation and matrix factorization, and practical implementation of the methods shown is explained through numerous examples. An introduction to MATLAB is included, together with a brief overview of modern software widely used in scientific computations. Outlines classical numerical methods, which is essential for understanding the principles and techniques of computer modellingIntended for use in a numerical methods course for engineering and science students, but will also be useful as a handbook on numerical techniques for research studentsCovers the basic ideas of numerical techniques, including iterative process, extrapolation and matrix factorization.